Clinical and laboratory differences between Epstein-Barr and cytomegalovirus infectious mononucleosis in children - Medović Raša (Srpski Arhiv za Celokupno Lekarstvo, 2016)
Introduction. Infective mononucleosis is most commonly caused by Epstein-Barr virus (EBV), and in smaller percentage by cytomegalovirus (CMV). Objective. The aim of this paper was to determine the clinical and laboratory differences between EBV and CMV infectious mononucleosis in children. Methods. Cohort retrospective analytical research was conducted. We used data from medical history in six years period and monitored anamnestic data, frequency of inspection and palpation obtained data during physical examination, several laboratory tests, abdomen ultrasonography examination finding and emergence of disease complications. Statistical processing of data has been performed using SPSS 20. Results. Total number of examined children was 137, out of which 85.4% were with EBV and 14.6% with CMV infection. Affected children were most commonly younger than eight years. Boys were affected more often. There was no difference in frequency of high temperature, sore throat, bad breath, and respiratory symptomatology between examined children. Differences were discovered in frequency of stomachaches, eyelid swelling, skin rash and fatigue. Differences were not proven in the frequency of angina, lymphadenopathy and splenohepatomegaly between the groups. Values of transaminases and lactic dehydrogenases significantly decreased after seven days of hospitalization in both groups. In children with EBV, values of transaminases declined faster than in children with CMV. Anemia and bacterial superinfection of pharynx were most common disease complications. Thrombocytopenia was more common in children with CMV infection. Average duration of hospitalization was 6.7 days. Conclusion. In children with CMV abdominal pain, eyelid swelling, skin rash, fatigue and thrombocytopenia were more common. In children with EBV values of transaminases declined significantly faster.